Impact of COVID-19 vaccine on clinical characteristics and outcome of hospitalized COVID-19 patients during the fourth wave of the pandemic in Tuzla Canton, Bosnia and Herzegovina - Humera Porobić-Jahić; Dilista Piljić; Rahima Jahić; Medina Mujić; Alma Trnačević; Jasminka Petrović; Sehveta Mustafić; Nedim Jahić; Nijaz Tihić (Medicinski glasnik, 2022)
Aim: To evaluate clinical and epidemiological characteristics and outcome of patients with COVID-19, and impact of vaccine against COVID-19 on them. Methods: This retrospective study included 225 patients treated from COVID-19 in the period from 1 to 30 September 2021 at the Clinic for Infectious Diseases, University Clinical Centre Tuzla (UCC Tuzla). For the diagnosis confirmation of Covid-19, RTPCR was used. Patients were divided in two groups: fully vaccinated with two doses of vaccine, and non-vaccinated or partially vaccinated. Results: Of 225 patients, 120 (53.3%) were females, and 105 (46.7%) males. Mean age was 65.6 years. There were 26 (11.6%) fully vaccinated patients. Most common symptoms in unvaccinated patients were fatigue (70.9%), cough (70.4%) and fever (69.8%), and in vaccinated fever (76.9%), fatigue (69.2%) and cough (46.2%). Cough was more common in unvaccinated patients (p=0.013). Fatal outcome happened in 84 (37.3%) patients. Transfer to the Intensive Care Unit (ICU) and older age had a higher risk of death (p<0.001). Older age patients were more likely to have comorbidities like atrial fibrillation (p=0.017), hypertension (p<001) and diabetes mellitus (p=0.002). Atrial fibrillation (p<0.001), hypertension (p<0.001), diabetes mellitus (p=0.009) and history of stroke (p=0.026), were related to fatal outcome in unvaccinated patients, also did a shorter duration of illness prior to hospitalization (p<0.001) and shorter length of hospitalization (p=0.002). Conclusion: Older patients with comorbidities, as well as those who were not vaccinated against COVID-19, were at higher risk for severe form of the disease and poor outcome.
Keywords: age; comorbidities; COVID-19; symptoms; vaccination